1990
DOI: 10.1128/mcb.10.9.4935
|View full text |Cite
|
Sign up to set email alerts
|

SPT6, an essential gene that affects transcription in Saccharomyces cerevisiae, encodes a nuclear protein with an extremely acidic amino terminus.

Abstract: SPT6 is an essential gene of Saccharomyces cerevisiae that appears to play a role in transcription. Mutations in the SPT6 (SSN20, CRE2) gene suppress 8 insertion mutations in the 5' regions of HIS4 and LYS2 and mutations in cis-and/or trans-acting elements that are required for expression of SUC2 and ADH2. We report here that SPT6 encodes a 170-kilodalton highly charged protein with an extremely acidic amino terminus. By use of an epitope-tagged SPT6 protein, we have determined by indirect immunofluorescence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…Malone et al (32) have demonstrated that both overexpression (by increased copy number) and mutation of the CDC681SPT16 gene result in suppression of 8-element insertion mutations. In this respect the CDC681SPT16 gene is similar to the SPT5 (60) and SPT61SSN201CRE2 genes (6,59). Both SPT5 and SPT6 encode essential nuclear proteins with extremely acidic N termini and have been suggested to influence gene expression through a function in chromatin assembly or modification.…”
Section: Discussionmentioning
confidence: 91%
“…Malone et al (32) have demonstrated that both overexpression (by increased copy number) and mutation of the CDC681SPT16 gene result in suppression of 8-element insertion mutations. In this respect the CDC681SPT16 gene is similar to the SPT5 (60) and SPT61SSN201CRE2 genes (6,59). Both SPT5 and SPT6 encode essential nuclear proteins with extremely acidic N termini and have been suggested to influence gene expression through a function in chromatin assembly or modification.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, histone octamers, but not H3-H4 tetramers, efficiently repress 5S RNA transcription in vitro (Tremethick et al 1990;Almouzni et al 1991). This model also raises the possibility that proteins functionally related to histones, such as the acidic SPT5 and SPT6 proteins (Swanson et al 1990, could repress transcription by stabilizing the interaction of H2A-H2B dimers with DNA-bound H3-H4 tetramers, in a manner analogous to that of the acidic chromatin assembly factor nucleoplasmin (Dingwall et al 1987). Other proteins implicated in affecting chromatin structure, including SIN1/SPT2, SPT4, and SPT16 Malone et al 1991;Swanson and Winston 1992), might also affect histone-histone or histone-DNA interactions.…”
Section: Genes and Developmentmentioning
confidence: 99%
“…The C-terminal region of mouse Spt6 binds the Ser-2-phosphorylated CTD, 2 suggesting a mechanism for how Spt6 is recruited to elongating RNA polymerase II (12). The Spt6 C-terminal region was predicted to contain an SH2 domain.…”
Section: The Tandem Sh2 Domain Is Apparently Required For Transcriptimentioning
confidence: 99%
“…Spt6 is an essential nuclear protein (1,2) that is required for transcription elongation together with Spt4 and Spt5 (3,4). Spt6 co-localizes with Spt5 on transcribed genes in Drosophila polytene chromosomes (5,6).…”
Section: The Tandem Sh2 Domain Is Apparently Required For Transcriptimentioning
confidence: 99%